A probe of social media marketing and binge-watching on customer loyalty of SVOD Netflix - Tannya Aprillia Rahayu Putri, Ni Putu (Review of Management, Accounting, and Business Studies, 2021)
In times of pandemic, the spread of internet users in their introduction can change most of the media, especially in the world of cinema. In the current pandemic situation with the company's latest earnings release, Netflix only added 5.5 million subscribers in the first half of 2021, whereas in 2020 Netflix's record rose to 36 million subscribers. The popularity of K-drama is increasing during the pandemic which makes consumers binge-watching. Thus, this study aims to determine the effect of social media marketing and binge-watching partially and simultaneously on customer loyalty. This research is important, especially in Indonesia, given the differences in Binge-Watching behavior towards consumer loyalty at the beginning of the pandemic and during the Covid-19 pandemic. The population uses those who already have a Subscribe Video on Demand (SVOD) platform, namely Netflix, and a sample of 100 respondents. The data analysis technique uses a Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, Coefficient of Determination Test, F Test, and t Test. The results of the study obtained the results: (1) social media marketing has a significant positive effect on customer loyalty, (2) binge-watching has a significant positive effect on customer loyalty, and (3) simultaneously social media marketing and binge-watching has a significant effect on customer loyalty which obtained a significance value of 0.000 <0.05. The magnitude of the influence of the independent variable on customer loyalty is 51.5%. For further research in order to examine more deeply other factors not examined in this study.